Visão de natureza: uma análise sobre práticas jurídicas antropocêntricas do Tribunal de Justiça do Estado do Rio Grande do Sul - Dias, Eugênia Antunes (2008)
Permanent Preservation Areas (APP s), specially in Brazil s coastal region, have been constantly occupied and degraded by anthropic activities which thrive on the hegemonic model built and consolidated trough a social-historic process that constitute the current relationship between Nature and human society an exteriorization of Nature and its submission to mostly economic interests the anthropocentric view of Nature. In its essence, the juridical field, including environmental law, is a form of softened anthropocentrism that contributes to the annihilation of other kinds of relationships between humans animals and Nature, among them the ecocentric view defended by the environmental movement. This qualitative study focused on unraveling and understanding the vision of Nature s privilege in the juridical practice of the Court of Justice of the State of Rio Grande do Sul (TJ/RS) based on the analysis of decisions and general manifestations of agents of the Judiciary Power when solving conflicts between commercial occupations in APP s and the local Executive Power at Laranjal Beach, Municipality of Pelotas, State of Rio Grande do Sul, Brazil. To exercise its obligation of fulfilling the fundamental right of an ecologically balanced natural environment, the local Executive Power, from 2001 onwards, initiated the process of administrative regularization of the area. This study revealed that the TJ/RS reverberated the anthropocentric view of Nature when pronouncing the custody of APP s and judging in contumacy of the protective law. The anthropocentric view of Nature is difficult to overcome, since its symbolic power and practical utility are strongly impregnated in contemporary societies. Despite the fact that the application of Environmental Law can secondarily protect Nature without the appraisal of utilitarian values, in practical terms the verified motivations reject this possibility.